Guatemala : Statistical Annex. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The paper presents statistical data on comparative social indicators, selected economic indicators, selected national accounts aggregates, summary expenditure and savings, summary consumer price indices, summary operations of the combined public sector, and summary of central government operations of Guatemala. The data on real gross domestic expenditure, labor productivity indicators, trends in unit labor costs, real wages, productivity, and employment, nonfinancial public sector operations, summary accounts of the financial system, detailed balance of payments, and imports by origin, and related economic indices are also presented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet